Networking chemical robots for reaction multitasking - Dario Caramelli (Nature Portfolio, 2018)
Distributing a reaction workload across laboratories can solve chemical problems more efficiently, but it is challenging to develop viable hardware and software. Here, the authors present an internet-connected network of cheap robots that can perform chemical reactions and share outcomes in real time, demonstrating a digitized approach to chemical collaboration.